MAKNA SIMBOL PROPERTI DALAM TARI NGAJAT LESUNG DI DESA SELUAS KABUPATEN BENGKAYANG - Mantiral, Vincentia Sepriana; Istiandini, Winda; Istiandini, Winda; Fretisari, Imma; Fretisari, Imma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research background was the symbolic meaning that needs to be expressed relating the use of wooden mortar/lesung in Ngajat Lesung dance. The research purposes were 1) Describing the meaning of the Ngajat Lesung dance property symbol based on its function and symbol based on its form. 2) Describing the cultural values that exist in Ngajat Lesung to build characters of the students. Method of this research was descriptive analysis. The research design in this research applied qualitative. The research approach used anthropology and iconography. The results of this research were 1) the meaning of the mortar/lesung property symbol based on its function as a medium in expressing it in dance. Lesung symbolized a power because male dancers expressed it by being bitten while dancing to show their strength. 2) The meaning of property symbols based on its form, namely the strengths that complement each other, and Bhineka Tunggal Ika. 3) Cultural values contained in the meaning of property symbols of Ngajat Lesung dance were values of discipline, values of courage, values of confidence, and solidarity. The results of this research were expected to be references for the Cultural Artsteachers in building character of students through learning dance in school.Â Keywords: The Meaning of Symbol, Dance Property, Ngajat Lesung